Iridescent Kuwait Petro-Modernity and Urban Visual Culture since the Mid-Twentieth Century - Hindelang, Laura (De Gruyter, 2021)
Petro-modernity is a local phenomenon essential to the history of Kuwait, while also a global experience and one of the prime sources of climate change. The book investigates petroleum's role in the visual culture of Kuwait to understand the intersecting ideologies of modernization, political representation, and oil. The notion of iridescence, the ambiguous yet mesmerizing effect of a rainbowlike color play, serves as analytical-aesthetic concept to discuss petroleum's ambiguous contribution to modernity: both promise of prosperity and destructive force of socio-cultural and ecological environments. Covering a broad spectrum of historical material from aerial and color photography, visual arts, postage stamps, and master plans to architecture and also contemporary art from the Gulf, it dismantles petro- modernity's visual legacy.